Breaking the curse: Addressing chronic malnutrition in the Philippines using a health system lens - Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2021)
Widespread chronic malnutrition in the Philippines is a human development disaster, which needs critical and urgent attention. Its consequences are multifaceted and extreme. Hence, it should be at the front and center of economic and health dialogue. This paper provides the current state of child stunting, a marker of chronic malnutrition. Using a health system lens, we have identified different challenges impeding the delivery of cost-effective health and nutrition interventions. Also, we provided health system-specific solutions in addressing the problem.
Keywords: 330; malnutrition; child stunting; health systems